Caffeine consumption within British fencing athletes - Morris, George Bowra; Manders, Ralph Johannes Francisca; Hulton, Andrew Thomas (Frontiers in Nutrition, 2022)
The ergogenic effects of caffeine are well documented, yet despite the potential benefits of supplementation, there is a lack of understanding of caffeine habits and supplementation within fencing. British fencers (n = 136) completed a Web-based questionnaire, exploring self-reported caffeine consumption, reasons for use and education. Fencers (94.1%) habitually consumed caffeine, primarily due to the taste of the products (93.8%). Respondents ingested 183.4 ± 137.5 mg of caffeine daily, with a significant difference between age groups (p < 0.05). Many respondents (30.1%) consumed caffeine 60 mins prior/during fencing training and/or competition with the main reason highlighted as cognitive performance enhancement. Respondents ingested 140.8 ± 104.6 mg of caffeine during training/competition, mainly as energy drinks, bars, and powders. Education on caffeine supplementation was low (25.7%), with significant associations between age groups (p < 0.05). Evidence implies caffeine toxicity has been experienced by 35% of fencers, highlighting the need for education on caffeine consumption. To conclude there is evidence of caffeine supplementation in fencing, primarily to magnify cognitive performance. However, there is a requirement for targeted education on caffeine supplementation to fencers, so that negative side effects and potential anti-doping infringements can be avoided.